REVIEW: PENGARUH METODE BUDIDAYA TERHADAP NILAI RASIO KONVERSI PAKAN (FCR) IKAN NILA SALIN (Oreochromis niloticus) DENGAN PENDEKATAN KOMPARATIF DARI SPESIES SEJENIS - Ramadhan, Luthfi Naufal; Haetami, Kiki (Universitas Mataram, 2025)
Tilapia salin (Oreochromis niloticus) is one type of fish for consumption that has economic value and quite high market demand in Indonesia because of its savory meat taste (Baihaqi et al. 2024). In fisheries cultivation, one important aspect in fish farming activities is feed management. This is because it can affect the growth rate of fish and the resulting feed conversion ratio (FCR) value (Budayati et al. 2023). The feed conversion ratio (FCR) value is one of the parameters used to assess the efficiency of feed utilization by fish. This research method uses a qualitative descriptive method with a literature review approach that examines and describes the results of previous studies regarding the effect of cultivation methods on the feed conversion ratio (FCR) value in tilapia salin (Oreochromis niloticus) in Indonesia. This study shows that the cultivation method has a significant effect on the feed conversion ratio (FCR) value in tilapia salin (Oreochromis niloticus). The biofloc system provides the best efficiency with the lowest FCR value (up to 1.07), followed by the recirculation system (RAS) and floating net cages (KJA) with relatively low and stable FCR values. In contrast, the pond system shows the most variable FCR values, even tending to be high, especially if water quality and feed management are not maintained.